Social Comic Commentary - an exploration of contemporary identity constructions - Hirsch, Anne (Department of Drama, 2024)
The focus of this research is the exploration of what I perceive as an emerging new culture, evolving, developing and shaping with a seemingly unstoppable force. For the purposes of my research I will refer to this collection of social and cultural practices and the participants that adhere to its rituals as the Nano-Culture; Nano referring to nanosecond, which is extremely quick. Nano-Culture is born out of a consumer culture, the age of technology and an all pervasive media. Furthermore I suggest that participants of this culture manage identity as brands, in order to present identity as desirable for consumption. Finally I propose a comedy that draws on the culture, assists in managing the culture and its constructed identities and ultimately critiques the culture. The following written submission is divided into two parts.